Pembuatan Sensor SnO₂ untuk Memantau Multi-Parameter dalam Proses Pembusukan Makanan - Moh. Toifur; Indra Budi Setiawan; Ishafit; Ridlo Hajatulloh; Okimustava; Eko Susanto (Universitas Nurul Huda, 2025)
This study reports the development of a tin dioxide (SnO₂)-based gas sensor fabricated via the electroplating method for monitoring food spoilage. Urap vegetables were used as test samples to investigate variations in temperature, CO₂ concentration, humidity, and sensor resistance during the spoilage process. The results revealed that the SnO₂ sensor exhibited a clear response to temperature and CO₂ concentration, both of which showed a consistent decrease in resistance with increasing values. In contrast, no definitive correlation between resistance and humidity was observed. These findings highlight the potential of electroplated SnO₂ sensors as multi-parameter devices for real-time food spoilage monitoring. Such an approach could be further optimized for practical applications in smart packaging and food quality control, thereby supporting food safety and waste reduction.